Efektivitas Model Pembelajaran LOK-R dalam Mata Pelajaran IPS Berbasis Pendekatan Literasi Digital pada Siswa - Siska Dwi Purwanti; Andrea Salsalova; Mu'arifah Mu'arifah; Djono Djono (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study examines the effectiveness of the LOK-R (Literacy, Orientation, Association, Reflection) learning model in Social Studies (IPS) learning in response to the rapid development of digital technology and the increasing need for digital literacy in education. The purpose of this study is to determine the effectiveness of LOK-R, which integrates digital literacy into classroom learning practices, as well as to encourage critical thinking, collaboration, and independent learning skills among students. The method used in this study is a literature study or review by analyzing various scientific sources such as indexed journals, reference books, and reliable digital publications. The results indicate that the LOK-R model significantly enhances student engagement and academic performance by aligning digital literacy skills with SSE learning content. In addition, the syntactic structure of this model helps students access, analyze, and produce digital information effectively. This study concludes that the LOK-R model is an innovative pedagogical approach to fostering 21st-century competencies and is recommended for wider implementation in the context of technology-based social learning.